2011
DOI: 10.1111/j.1365-3113.2010.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

On the head morphology of Grylloblattodea (Insecta) and the systematic position of the order, with a new nomenclature for the head muscles of Dicondylia

Abstract: External and internal head structures of adults of Galloisiana yuasai (Grylloblattodea) are described. The results are compared with conditions found in representatives of other lower neopteran lineages, notably in Austrophasma and Karoophasma (both Mantophasmatodea). Sutures and ridges of the head capsule are discussed. A new nomenclature for head muscles is presented for the entire Dicondylia (= Zygentoma + Pterygota). Galloisiana (like its sister taxon Grylloblatta) is mostly characterized by plesiomorphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 114 publications
(139 citation statements)
references
References 48 publications
(264 reference statements)
5
133
0
1
Order By: Relevance
“…In many 'higher' insects such as certain Grylloblattodea, Mantodea and Orthoptera, a part or all of muscles 0md5-8 are absent (Blanke et al, 2012). We therefore suggest that muscles 0md5-8 do not play a crucial role during biting in winged insects like Ephemeroptera, Odonata and Polyneoptera and accordingly were reduced in some higher lineages of insects [see character matrices in, for example, Blanke et al (2012Blanke et al ( , 2013a and Wipfler et al (2011) for presence/ absence of these muscles within winged insect orders].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many 'higher' insects such as certain Grylloblattodea, Mantodea and Orthoptera, a part or all of muscles 0md5-8 are absent (Blanke et al, 2012). We therefore suggest that muscles 0md5-8 do not play a crucial role during biting in winged insects like Ephemeroptera, Odonata and Polyneoptera and accordingly were reduced in some higher lineages of insects [see character matrices in, for example, Blanke et al (2012Blanke et al ( , 2013a and Wipfler et al (2011) for presence/ absence of these muscles within winged insect orders].…”
Section: Discussionmentioning
confidence: 99%
“…As we follow the terminology of Beutel et al (2013) and Wipfler et al (2011), and to allow for comparison with the literature record, we retained the term 'tendon' here. Because of this sclerotization, the material properties of this structure cannot be compared with tendon-like structures in, for example, vertebrates.…”
Section: Tendonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autapomorphies include prothoracic defense glands and small, pyriform appendages on the posterior midgut (tilgner et al 1999(tilgner et al , Beutel et al 2013 recently demonstrated as having a unique excretory function (Shelomi & Kimsey 2014). the sister order to the phasmatodea is most likely embiidina (webspinners) forming a "eukinolabia" clade, based on external morphology (Wipfler et al 2011, Friedemann et al 2012, Beutel et al 2013, rdnA (Flook & Rowell 1998, terry & Whiting 2005, expressed sequence tags (letsch et al 2012) and transcriptomics (Misof et al 2014). Future phylogenetic analyses are still required to resolve the relationships of the polyneopteran orders (trautwein et al 2012): in particular, comparisons of internal features are lacking due to the inconsistent anatomical studies.…”
mentioning
confidence: 99%
“…The tissue contrast of pure absorption contrast data are, however, very high, and therefore SRmCT might be considered an excellent alternative to histological (Wirkner and Richter 2007) will help surmount these issues. Examples of articles using SRmCT to infer arthropod systematics include Beutel et al (2009a), Friedrich and Beutel (2010), Huckstorf and Wirkner (2011), Talarico et al (2011), Wipfler et al (2011) and Friedemann et al (2012. Researchers have also used SRmCT to explore the characteristics of obscured fossil insects in amber (Tafforeau et al 2006;Lak et al 2008) and to partially reconstruct the internal phenomes of fossil insects (Pohl et al 2010).…”
Section: Introductionmentioning
confidence: 99%